Edukasi Gerakan 3R (Reduce, Reuse, dan Recycle) Berbasis Isu Sosial pada Siswa Sekolah Dasar untuk Menumbuhkan Sikap Peduli Lingkungan di Kota Medan - Albi Anggito; Putri Roka Ismail; Andreas Lubis (Abdimas Mandalika, 2026)
Abstract:  The problem of plastic waste has become a significant socio-environmental issue in Medan City, along with the increasing activity of urban communities and the consumption of single-use products. This condition demands efforts to address it involving all elements of society, including school-age children as the next generation. This community service activity aims to assist elementary school students in implementing the 3R Movement (Reduce, Reuse, and Recycle) as an effort to instill environmental awareness and integrate socio-environmental issues into social studies learning. The community service implementation method uses an educational and participatory approach that includes interactive lectures, demonstrations, hands-on practice, and play activities tailored to the characteristics of elementary school students. Evaluation of the activity was carried out through structured observations to measure changes in students' understanding, attitudes, and behavior before and after the mentoring. Observation data were analyzed descriptively quantitatively to determine the level of change that occurred. The community service results showed improvements in all observed aspects, including understanding of waste management, waste sorting skills, environmental awareness, student participation, and social interaction. The average value indicates that the 3R Movement mentoring has a positive impact on student behavior. This activity fosters environmental awareness from an early age and supports the formation of environmentally conscious character in elementary school students. Thus, the 3R Movement mentoring has the potential to be developed as a model of sustainable service in community-based waste management efforts in Medan City.Abstrak: Permasalahan sampah plastik menjadi isu sosial lingkungan yang signifikan di Kota Medan seiring meningkatnya aktivitas masyarakat perkotaan dan pola konsumsi produk sekali pakai. Kondisi tersebut menuntut upaya penanganan yang melibatkan seluruh elemen masyarakat, termasuk anak usia sekolah sebagai generasi penerus. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk mendampingi siswa sekolah dasar dalam menerapkan Gerakan 3R (Reduce, Reuse, dan Recycle) sebagai upaya menanamkan kepedulian lingkungan integrasi isu sosial lingkungan dalam pembelajaran IPS. Metode pelaksanaan pengabdian menggunakan pendekatan edukatif dan partisipatif yang meliputi ceramah interaktif, demonstrasi, praktik langsung, serta aktivitas bermain yang disesuaikan dengan karakteristik siswa sekolah dasar. Evaluasi kegiatan dilakukan melalui observasi terstruktur untuk mengukur perubahan pemahaman, sikap, dan perilaku siswa sebelum dan setelah pendampingan. Data hasil observasi dianalisis secara deskriptif kuantitatif untuk melihat tingkat perubahan yang terjadi. Hasil pengabdian menunjukkan peningkatan pada seluruh aspek yang diamati, meliputi pemahaman pengelolaan sampah, kemampuan memilah sampah, kepedulian lingkungan, partisipasi siswa, serta interaksi sosial. Nilai rata-rata mengindikasikan pendampingan Gerakan 3R memberikan dampak positif terhadap perilaku siswa. Kegiatan ini menumbuhkan kesadaran lingkungan sejak dini serta mendukung pembentukan karakter peduli lingkungan pada siswa sekolah dasar. Dengan demikian, pendampingan Gerakan 3R berpotensi dikembangkan sebagai model pengabdian berkelanjutan dalam upaya pengelolaan sampah berbasis masyarakat di Kota Medan.